Gateway and naubatkhana at the Jagannath Mahadev Temple - Ghosh, Ayan (2023)
The Jagannath Mahadev Temple has one of the two naubatkhanas at Walkeshwar, the other being at Vyankatesh Balaji Temple. The naubatkhana is built over the arched gateway, though now the space is used for residential purposes by the current occupants of the temple, many of whom live as tenants. The arched gateway open to the street and is entered through a carved wooden door which opens to the inner courtyard.